Space remote sensing for monitoring seasonal dynamics of grasslands in high-altitude zones in Armenia - G. Ayvazyan; A. Medvedev; A. Hovsepyan; A. Khlghatyan; S. Asmaryan (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The study, effective management, and rational use of mountain grasslands are becoming increasingly important due to the threat of natural and human-induced degradation. In Armenia, this remains a critical issue that requires comprehensive monitoring and consistent management. The application of remote sensing provides an opportunity to detect stressed and harmed vegetation, which in turn helps to assess the state of biomass. In this study, remote sensing data were used to determine the state of pasture vegetation, which is an important forage base, in conditions of vertical zonation in a small area. In addition, the data were used to develop a rational grazing regime for pasture users. The results show that incorrect grazing practices are observed in certain landscape zones. Livestock breeding is mainly concentrated in the meadow-steppe zone, which can lead to overgrazing. Meanwhile, other zones are underutilized due to premature livestock relocation. This study aims to use remote sensing to assess the vegetation condition of grasslands located in altitudinal landscape zones during the growing season and, based on this, help users optimize grazing, organize rational grassland management, and avoid overgrazing.